(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
The audit profession today gets an increasing interest by the financial , economic and legal contemporary societies , because of the importance of the technical & neutral auditor’s opinion to the financial reports beneficiaries in order to enable them making their investment decisions , but some of them whom suffered damage or loss when they made that decisions according to the mentioned financial statements which consolidated with auditor’s report , exposed the function to a responsibility and credibility crisis in addition to missing the trust especially at the latest years. They always ask why or what is the reason that cause the auditor didn’t giving us any warning signs about the economic mater for that companies.